POLITENESS STRATEGIES USED BY THE PRESIDENTIAL CANDIDATES OF INDONESIA IN THE 2014 FINAL PRESIDENTIAL DEBATE - NURJANAH, FEBRIANA ARUM (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Politeness, Face Threatening Act (FTA), Politeness Strategy, Debate.As social creatures, people need to interact with others. Sometimes, people do an action that threaten their interlocutor’s face when having communication. Therefore, people should consider the politeness aspects and apply the politeness strategy to minimize the face threat. The writer conducted a study about FTA and politeness strategies occuring in the 2014 final presidential debate. There are two problems of the study that are proposed by the writer: (1) What face is threatened by each presidential and vice presidential candidates in the final debate and (2) What are the types of politeness strategies performed by the presidential and vice presidential candidates in the final debate.This study used qualitative approach to gather and analyze the data. It was included into document analysis because it analyzed the script and conversations performed by the 2014 Indonesia presidential candidates.From the result of the analysis, there were 28% of utterances that contain face threatening acts and politeness strategies performed by the presidential candidates of Indonesia. Also it showed that most of the candidate frequently threatened other candidates’ negative face and they used positive politeness strategies more often than the other strategies. It indicates that each candidate wanted to still maintain a good relation to each other.The writer suggests the next researchers to analyze face threatening acts and politeness strategies in other media such as in a live talkshow. They can also analyze debate program using other field of study like Critical Discourse Analysis to know the power and ideology behind a debate.